Imersão: sensação redimensionada pelas tecnologias digitais na arte contemporânea - Silveira, Greice Antolini (2011)
This Master Thesis goals the comprehension of the enlargement that digital images add to the art field, specially the immersion feeling. It is thought that the feeling that the observer is inside the images is intensified by artistic experiences with digital technology, in this way it seems to be important to discuss such subject in a contemporary context, searching for some differences of the idea of immersion into images before and after digital technologies. To understand this transition from analog to digital image, that could be talks to as the production of image, considering the difference of being in front of, amid or in the image, besides explaining about the passage from observation to interaction between the art work and the interactor. Being within an ambient or not depends primarily on the comprehension of reality, so it is presented in this study discussions on reality, some questions on virtual and virtual reality Some devices are approached, so their contribution to the thinking of the feeling of immersion in artistic images relating it with current trend and getting in digital devices aside from showing some immersion levels suggested by researchers. For some detailed forthcoming the following art works will be analyzed: Osmose (2005) by Chair Davies and VRAquarium (2005) by Diana Domingues and Artecno team. Images that fullfil 360 grades from the observer sight can be found among all the Art History; some of them were made in order to cause in the spectator an immersion feeling in the presented scene. Therefore the attempt to comprehend the possible modifications that digital imaging provide to the Arts, especially the feeling of immersion, demonstrates itself as pertinent to understand how images can be presented at contemporary times.